Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Cumulative Review - Page 913: 22



Work Step by Step

$\sqrt[3] (64x^{7}y^{2})=\sqrt[3] (64x^{6}\times xy^{2})=\sqrt[3] (64x^{6})\times \sqrt[3](xy^{2})=4x^{2}\sqrt[3]xy^{2}$ We know that $\sqrt[3] (64x^{6})=4x^{2}$, because $(4x^{2})^{3}=4^{3}x^{2\times3}=64x^{6}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.